Model Relationship Between Performance Criteria And The Most Significant Accounting Of Value-Based Criteria : Economic Added Value (EVA) - Sari, Rafika; Meiriasari, Vhika (Dinasti Publisher, 2024)
Monetary patrons make informed decisions by assessing positive pointers that an association could show from this point forward, rather than relying altogether upon its evident execution. Consequently, this assessment plans to explore the relationship between execution norms and the main worth based estimation: Monetary Added Worth (EVA). Besides, it investigates what future EVA values mean for a bank's overall worth. The audit uses Board Data Examination and OLS Backslide models to assess the backslide condition. The audit separated data from ten banks in the BIST Banks Rundown spreading over the period from 2011 to 2020. In this manner, the Monetary Added Worth (EVA) measures were changed into standardized EVA (SEVA) by parceling EVA by full scale assets. The eventual outcomes of the Standard Least Squares (OLS) backslide assessment showed that the model's illustrative power for the SEVA variable was 71.92%. Extraordinarily, three variables showed positive associations with SEVA: benefit per share (EPS) and TOBINQ at a significance level of 1%, as well as the improvement speed of cost to-bargains at a significance level of 10%. Concerning Board Data Assessment, the SEVA variable showed an illustrative power of 72.14%, with a basic relationship saw among SEVA and the EPS and TOBINQ measures at the 1% significance level. Observational revelations recommend that including future SEVA as a mediator for bank regard holds responsibility, and it is recognized that the SEVA variable can go about as an intermediary measure for bank regard. Concerning Board Data Examination, the SEVA variable displayed a sensible power of 72.14%. Very, its relationship with the pay per share (EPS) and TOBINQ models was seen as immense at the 1% significance level. Careful assessments suggest that the model, which involves future SEVA as a middle person for bank regard, holds ensure. It is recognized that the SEVA variable can go about as a substitute measure for bank regard.